Epidemiology and lifestyle survey of non-alcoholic fatty liver disease in school-age children and adolescents in Shenyang, Liaoning - Guan Lin; Zhang Xinhe; Tian Haoyu; Jin Xing; Li Dan; Wang Ningning; Sun Jing; Wang Xue; Zeng Zilu; Li Yiling (BMC, 2022)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is diagnosed increasingly in children and adolescents. We aimed to investigate the prevalence and related influencing factors of NAFLD in school-aged children and adolescents in Shenyang, Liaoning Province. Furthermore, we analyzed the relationship between lifestyle and fatty liver. Methods We conducted aprospective cohort study of 1309 school-aged children and adolescents between the ages of 7 and 18 years who underwent physical examination from November to December 2019. In addition, they were collected age, gender, learning stage, height, weight, BMI, waist circumference, hip circumference, and waist-hip ratio. Finally, a portion of the population was selected to complete a questionnaire survey to explore the impact of lifestyle habits on fatty liver disease. Results NAFLD was present in 23.83% of subjects. The prevalence of children and adolescents was 22.73% and 24.43%, respectively. Fatty liver prevalence differs significantly by gender and learning stages. The highest rate of fatty liver was seen in obese children (71.68%). Moreover, exercise, diet, and parental factors can affect children with fatty liver. Conclusions NAFLD is very prevalent in children and adolescents in Shenyang city. Due to the close relationship between NAFLD and obesity, lifestyle plays a major role in the occurrence of NAFLD. Trial registration The First Affiliated Hospital of China Medical University, [2020] 2020-258-2. Registered 6 June 2020-Retrospectively registered.